Improvement of BLASTp on the FPGA-Based High-Performance Computer RIVYERA - Wienbrandt, Lars; Siebert, Daniel; Schimmler, Manfred (Bioinformatics Research and Applications, 2012)
NCBI BLASTp plays the major role of protein database searches already for years. However, with today’s growth of sequence database sizes, it becomes more inefficient with standard PC architectures. One solution to address this problem was already presented in our previous implementation, published in [16], taking advantages of the massive parallelization provided by the FPGA-based high-performance computer RIVYERA [3]. The analysis of bottlenecks in our BLASTp pipeline showed the urgent need to speed up the two-hit finder component, as well as the postprocessing on the PC. After a complete redesign of the two-hit finder and the insertion of a new “gapped extension” filter, we achieve a speedup of up to 376, compared to one thread of a fully utilized 2x Intel Xeon E5520 PC system at $2.26\ensuremath{GHz} $ running original NCBI BLASTp v. 2.2.25+. This is about two times the performance of our previous implementation.